Investigation of a dilated cardiomyopathy–associated variant in BAG3 using genome-edited iPSC-derived cardiomyocytes - McDermott-Roe, Chris (JCI Insight, 2019)
Mutations in B cell lymphoma 2–associated athanogene 3 (BAG3) are recurrently associated with dilated cardiomyopathy (DCM) and muscular dystrophy. Using isogenic genome-edited human induced pluripotent stem cell–derived cardiomyocytes (iPSC-CMs), we examined how a DCM-causing BAG3 mutation (R477H), as well as complete loss of BAG3 (KO), impacts myofibrillar organization and chaperone networks. Although unchanged at baseline, fiber length and alignment declined markedly in R477H and KO iPSC-CMs following proteasome inhibition. RNA sequencing revealed extensive baseline changes in chaperone- and stress response protein–encoding genes, and protein levels of key BAG3 binding partners were perturbed. Molecular dynamics simulations of the BAG3-HSC70 complex predicted a partial disengagement by the R477H mutation. In line with this, BAG3-R477H bound less HSC70 than BAG3-WT in coimmunoprecipitation assays. Finally, myofibrillar disarray triggered by proteasome inhibition in R477H cells was mitigated by overexpression of the stress response protein heat shock factor 1 (HSF1). These studies reveal the importance of BAG3 in coordinating protein quality control subsystem usage within the cardiomyocyte and suggest that augmenting HSF1 activity might be beneficial as a means to mitigate proteostatic stress in the context of BAG3-associated DCM.